До питання про співвідношення індивідуальної і колективної ідентичності: самоідентифікація індивіда як механізм соціальної пам’яті - Мазур, Любов (Видавництво Львівської політехніки, 2014)
На основі історико-генетичного методу розкрито функціональний взаємозв’язок між самоідентифікацією індивіда і пам’яттю: фіксація суспільного досвіду та його трансформація в елементи індивідуального уможливлювалася і забезпечувалася шляхом розрізнення себе від іншого, що підвищувало значимість фактору новизни і взаєморозуміння у процесі комунікації. Оскільки пам’ять утримується взаємною самоідентифікацією з іншим, вона є соціальною за формою і змістом. Беручи до уваги ці моменти, автор вважає доцільним розрізняти стихійну самоідентифікацію індивіда на повсякденному рівні і становлення особистісної самоідентичності та формування колективних ідентичностей на основі рефлексії і відповідних практик. According to the author, one-sidedness of holistic and individualistic methodology in the interpretation of individual correlation and collective identity can be overcome by the grounds of the historical-genetic method that quite clearly reveals the functional relation between selfidentity and memory in the process of socialization of individual. Powerful factor in the growth of the working memory and the structure of the subjective world of man was differentiation and complexity of social communication and related languages. Coding of the external and subjective worlds with the abstract symbols made the world of inner feelings available for other people, forming a single mechanism of self-identification for individuals and the transformation of social experience into individual elements, what in its own way increased the importance of the novelty factor. Exactly on the edge with another in their mutual selfidentification there is a body of memory, which gives every feeling the definite quality of continuation in other. According to the author, since the memory by its form and content is social and separate individuals becomes its carriers, we can say that the division of the identity into individual and social ones, neither by its carrier nor by the performance level, has no grounds. On the other hand, the author considers it reasonable to distinguish between identity formation at the everyday life level, where the identity of the other occurs almost automatically at a subconscious level and between the identity over its limits, when the holiday, game, art, theater, sacral, etc., bring something new to life, give moments of flight - it broaden the existing boundaries, сhanging constant structures, causing reflection and making people work on themselves. A personal identity is the result of reflection and application of practices to themselves. As the sociability is given to a man itself, fully implicit and therefore not perceptible, as a result it cannot give any individual neither we-consciousness nor self-identity. Collective identity can be formed, provided that the community is recognized and consciously is supported. Its importance lies in the fact that it forms a canon which becomes a tool of identity individualization in the process of its socialization. Canon as a criterion for evaluation is the mediating link between “I am”-identity and collective identity.
To the question about correlation of individual and collective identity: self-identification of individual as mechanism of social memory
Keywords: особистісна самоідентичність; колективна ідентичність; соціальна пам'ять; канон; самоідентифікація з іншим; соціалізація; personal self-identity; collective identity; social memory; canon; self-identification with other; socialization